Infectious risk assessment of unsafe handling practices and management of clinical solid waste - Hossain, Md. Sohrab; Nik Ab Rahman, Nik Norulaini; Balakrishnan, Venugopal; Puvanesuaran, Vignesh; Sarker, Md. Zaidul Islam; Kadir, Mohd Omar Ab (MDPI, 2013)
The present study was undertaken to determine the bacterial agents present in various clinical solid wastes, general waste and clinical sharp waste. The waste was collected from different wards/units in a healthcare facility in Penang Island, Malaysia. The presence of bacterial agents in clinical and general waste was determined using the conventional bacteria identification methods. Several pathogenic bacteria including opportunistic bacterial agent such as Pseudomonas aeruginosa, Salmonella spp., Klebsiella pneumoniae, Serratia marcescens, Acinetobacter baumannii, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Streptococcus pyogenes were detected in clinical solid wastes. The presence of specific pathogenic bacterial strains in clinical sharp waste was determined using 16s rDNA analysis. In this study, several nosocomial pathogenic bacteria strains of Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Lysinibacillus sphaericus, Serratia marcescens, and Staphylococcus aureus were detected in clinical sharp waste. The present study suggests that waste generated from healthcare facilities should be sterilized at the point of generation in order to eliminate nosocomial infections from the general waste or either of the clinical wastes.